2017
DOI: 10.18632/oncotarget.15401
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA, treRNA, decreases DNA damage and is associated with poor response to chemotherapy in chronic lymphocytic leukemia

Abstract: The study of long noncoding RNAs (lncRNAs) is an emerging area of cancer research, in part due to their ability to serve as disease biomarkers. However, few studies have investigated lncRNAs in chronic lymphocytic leukemia (CLL). We have identified one particular lncRNA, treRNA, which is overexpressed in CLL B-cells. We measured transcript expression in 144 CLL patient samples and separated samples into high or low expression of treRNA relative to the overall median. We found that high expression of treRNA is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Numerous lncRNAs are deregulated in different sorts of malignant growths, including head and neck cancer [92]. Unmistakable expression profiles of lncRNA have been distinguished in leukemia [9,33,35,45,[47][48][49][93][94][95][96][97][98][99]. Some of these have been demonstrated to have wellunderstood jobs in the development and progression of leukemia, suggesting the vital use of lncRNAs as novel biomarkers and potential targets for the treatment of leukemia.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Numerous lncRNAs are deregulated in different sorts of malignant growths, including head and neck cancer [92]. Unmistakable expression profiles of lncRNA have been distinguished in leukemia [9,33,35,45,[47][48][49][93][94][95][96][97][98][99]. Some of these have been demonstrated to have wellunderstood jobs in the development and progression of leukemia, suggesting the vital use of lncRNAs as novel biomarkers and potential targets for the treatment of leukemia.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Another lncRNA, treRNA, is highly expressed in patients with aggressive CLL, bearing poor prognostic indicators such as unmutated IGHV and high ZAP70 protein expression. In this set of patients, treRNA expression is associated with shorter PFS and OS, and a low expression of treRNA has been proven to be an independent prognostic factor for improved PFS in patients receiving fludarabine plus cyclophosphamide [53] BGL3 (beta globin locus transcript 3) is a 3.6-kb lncRNA derived from chromosome 11p15.4. BGL3 expression in leukemic cells is negatively regulated by Bcr-Abl through c-Myc-mediated DNA methylation [54].…”
Section: Genomic Instability and Mutationsmentioning
confidence: 99%
“…A microarray study identified eight lncRNAs differentially expressed in CLL patients compared to controls. One of these, translation regulatory long non-coding RNA1 (treRNA1) was significantly higher expressed in unmutated IGHV samples [ 95 ], and served as an independent prognostic marker for shorter PFS in patients receiving fludarabine and cyclophosphamide. Overexpression of treRNA1 in a CLL cell line led to reduced cell death, suggesting that treRNA1 decreases DNA damage and sensitivity to chemotherapy, thereby explaining the shorter PFS.…”
Section: Long Non-coding Rna Expression In Various B-cell Malignanmentioning
confidence: 99%